THE ROLE OF TEXTBOOKS IN LANGUAGE LEARNING - Allanova Munira Mubarak qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, we describe language learning, its stages, and the role of textbooks in the language learning process. As learning a new language and improving knowledge is a requirement of the present time, the role of textbooks is incomparable.